2010
DOI: 10.1590/s0103-90162010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of lead by jack beans on a Rhodic Hapludox amended with EDTA

Abstract: A greenhouse study was conducted to evaluate the effects of ethylenediamine tetraacetic acid (EDTA) addition to soils on the lead (Pb) phytoextraction potential of jack beans (Canavalia ensiformis L.). In a pot experimentSoil samples (dystrophic Rhodic Hapludox) were treated with six Pb rates (0, 100, 200, 350, 1,200, and 2,400 mg kg-1 soil) applied as Pb(NO3)2 without and with EDTA application (0 and 0.5 g kg-1, respectively). Lead, Cl-, NO3-, NH4+, SO4(2-), H2PO4-, Zn2+, Cu2+, Fe3+, Al3+, Ca2+, Mg2+, K+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 37 publications
0
10
1
2
Order By: Relevance
“…Other authors (Paiva et al, 2000;Boonyapookana et al, 2005;Alves et al, 2008;Pereira et al, 2010;Danh et al, 2011;Seth et al, 2011;Zhivotovsky et al, 2011;Hamadouche et al, 2012;Hamvumba et al, 2014) also found reductions of dry matter production in many plant species as a function of the application of increasing doses of Pb in experiments with soil and nutrient solution. The Pb toxicity observed in the present study is due to its action on plants, causing physiological, biochemical and structural disorders, such as disequilibrium in water and hormone balance, nutritional disorders, loss of membrane permeability, reduction of enzymatic activity, inhibition of respiration and photosynthesis, among others (Yadav, 2010;Gupta et al, 2013).…”
Section: Resultsmentioning
confidence: 89%
“…Other authors (Paiva et al, 2000;Boonyapookana et al, 2005;Alves et al, 2008;Pereira et al, 2010;Danh et al, 2011;Seth et al, 2011;Zhivotovsky et al, 2011;Hamadouche et al, 2012;Hamvumba et al, 2014) also found reductions of dry matter production in many plant species as a function of the application of increasing doses of Pb in experiments with soil and nutrient solution. The Pb toxicity observed in the present study is due to its action on plants, causing physiological, biochemical and structural disorders, such as disequilibrium in water and hormone balance, nutritional disorders, loss of membrane permeability, reduction of enzymatic activity, inhibition of respiration and photosynthesis, among others (Yadav, 2010;Gupta et al, 2013).…”
Section: Resultsmentioning
confidence: 89%
“…The solubility and bioavailability of heavy metals can be improved by adding synthetic chelators such as ethylene diamine tetraeacetic acid (EDTA), diethylene triamine pentaeacetic acid (DTPA), and ethylene glycol tetraeacitic acid (AGTA), which enhance uptake by plants (Saifullah et al 2009;Pereira et al 2010). The molecules of the chelators bind the metal atom, thereby increasing its concentration in soil aqueous phase and its mobility (Wu et al 2010).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Some synthetic chelating agents, such as ethylene diamine tetraacetic acid (EDTA), diethylene triamine pentaacetic acid (DTPA) and ethylene glycol tetraacetic acid (EGTA) have been used successfully for induced phytoextraction (Pereira et al, 2010). However, the application of such synthetic chelating agents introduces an environmental risk due to their high mobility in the soil, which can result in the transport of the contaminant to uncontaminated surrounding areas; this movement can potentially become a problem due to the high solubility and persistence in the soil of the chelate-heavy metal complex (Luo et al, 2006;Quartacci et al, 2007).…”
Section: Synthetic Chelating Agentsmentioning
confidence: 99%